PEMIKIRAN DAN AKSI FEMINISME TOKOH PEREMPUAN DALAM NOVEL MATARAISA KARYA ABIDAH EL KHALIEQY - Ririen Wardiani; Yuniar Pratama Ajistria (Jurusan Tadris Bahasa Indonesia, 2016)
â€œMataraisaâ€, a novel written by Abidah El Khalieqy is interesting to be analyzed. This novel gives strong image of an intellectual woman who are dare to ekspress their idea about womenâ€™s right. The research focuses on discussing the feminist idea and action in â€œMataraisaâ€ novel by Abidah El Khalieqy.The purpose of this research is to describe the feminist ideaand action of the female characters in â€œMataraisaâ€ novel by Abidah El Khalieqy.This research used descriptive method and feminism analysis. The technique of collecting data is library research through studying the literatures discussing feminism. The research conclusion isthe feminist idea and action of female characters are purposed to get gender equality in their society. Concretely, it is shown in the field of freedom of speech, education, workload, and social life.